PARIWISATA HALAL BALI: STUDI KASUS PENERAPAN PARIWISATA HALAL OLEH NUSANTARA TOUR & TRAVEL TAHUN 2024 - Supardi, Supardi (International Journal Mathla’ul Anwar of Halal Issues, 2025)
Halal tourism has become a trending topic in the last decade, so it is not surprising that everyone involved in the world of tourism participates in studying, understanding, alluding to, supporting, opposing and even provoking positively and negatively towards this halal tourism. Bali carries tourism that emphasizes culture. Nature tourism in Bali is known as cultural tourism and is also referred to as the local wisdom of the Balinese people and is philosophically based on Hindu teachings (Darmawan, 2023; Risfandini, 2019). Therefore, there must be a role for stakeholders in efforts to develop halal tourism in Bali. This is because halal tourism is universal, not bound by a particular form that can prevent the island of the gods 'Bali' from developing halal tourism. Moreover, the prospects for the halal tourism business are very large because halal is not just about religion, but has become a choice, opportunity, and lifestyle. The purpose of this study is to find out Halal Tourism in Bali (Case Study of the Implementation of Halal Tourism by PT. Nusantara tour & travel)" the research method used is a case study and the results of this study are that the company welcomes halal tourism, sees this as an opportunity to expand the market and improve services to Muslim tourists, both domestic and international. As for support for the halal tourism program and its form, Nusantara T&T mentions several things that have become the main principles of halal tourism, namely the following aspects below. Providing various services that are in accordance with halal principles, ensuring halal food, providing prayer facilities, designing tour packages that suit the needs of Muslim tourists, working with restaurants whose food does not contain pork and drinks do not contain alcohol, and other ingredients that are classified as non-halal. The conclusion is that PT. Nusantara Tour & Travel strongly supports Halal Tourism in Bali, but does not brand tourism in Bali with halal tourism but still provides Muslim-friendly tourism.